2016
DOI: 10.1016/j.bmcl.2016.06.040
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of Minor Groove Binders as anti-lung cancer therapeutics

Abstract: A series of 47 structurally diverse MGBs, derived from the natural product distamycin, was evaluated for anti-lung cancer activity by screening against the melanoma cancer cell line B16-F10. Five compounds have been found to possess significant activity, more so than a standard therapy, Gemcitabine. Moreover, one compound has been found to have an activity around 70-fold that of Gemcitabine and has a favourable selectivity index of greater than 125. Furthermore, initial studies have revealed this compound to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
(5 reference statements)
1
13
0
Order By: Relevance
“…This is a cell line derived from cells that metastasized to the lung and were isolated from lung metastatic nodules. 13 In that study, we identified that subtle structural variations significantly influenced the activity profile of the S-MGBs. Significantly, we were able to identify an S-MGB with around a 70-fold greater activity than gemcitabine, a current treatment option used in the clinic for non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 95%
“…This is a cell line derived from cells that metastasized to the lung and were isolated from lung metastatic nodules. 13 In that study, we identified that subtle structural variations significantly influenced the activity profile of the S-MGBs. Significantly, we were able to identify an S-MGB with around a 70-fold greater activity than gemcitabine, a current treatment option used in the clinic for non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 95%
“…Several focused reviews on small molecule DNA binding agents have been published in recent years. A few have updated the progresses made in disease specific DNA binders [ 14 15 ] while others have included class specific or site-specific DNA binding agents [ 16 23 ]. A few others have covered nucleic acids binders in general [ 20 ] as well as an emerging therapeutic DNA target: the DNA G-quadruplex [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…Szerszenowicz et al developed a new set of potential minor groove binders derived from netropsin and bis-netropsin analogs by replacing N -methylpyrrole rings with other heterocyclic rings and their antiproliferative activity was tested on MCF-7 breast cancer cells [ 60 ]. Suckling et al recently designed and synthesized a series of structurally diverse MGBs, derived from distamycin, in order to test their lung cancer inhibition activity against the melanoma cancer cell line B16-F10 [ 14 ]. Conjugate 11 was found to be extremely potent and exhibits 70-fold activity in comparison to the standard therapy, gemcitabine.…”
Section: Reviewmentioning
confidence: 99%
“…Distamycin does not possess significant cytotoxicity; however, other classes of minor groove binders have shown significant possibility as anti-cancer agents, in particular those which are derived from the distamycin structure (Scheme 9). 45 …”
Section: Mgbs For the Treatment Of Lung Cancermentioning
confidence: 99%